A critical reflection on the principles of peroxisome formation in yeast - Van Der Klei, Ida J.; Veenhuis, Marten (Frontiers in Physiology, 2014)
We have evaluated the current knowledge on peroxisome proliferation in yeast. In wild-type cells, peroxisomes multiply predominantly by fission at conditions that require peroxisome function(s) for growth. In cells that lack peroxisomes, for instance in pex3 and pex19 mutants or in mutants that display inheritance defects, peroxisomes may form de novo. We propose a novel machinery for the de novo formation of peroxisomes in pex3 cells, in which new peroxisomes do not arise from the endoplasmic reticulum. This machinery is based on the recent observation that membrane vesicles are present in these cells that display peroxisomal characteristics in that they contain specific peroxisomal membrane and matrix proteins. These structures are the target for newly formed peroxisomes upon reintroduction of Pex3. Furthermore, we critically evaluate the principles of sorting of other peroxisomal membrane proteins to their target organelle and the function of the endoplasmic reticulum therein.